Appunti per un discorso sull’intimità - Masullo, Aldo (Bollettino Filosofico, 2019)
The present paper aims to analyze the diverse accents of the concept of “intimacy” through the linguistic, anthropological and literary nuances that constitute its rich meaning-framework, in order to reach an essential philosophical determination of this concept. This result is achieved through an initial exploration of the conceptual “geography” of the “dual”. Subsequently, the text focuses on the ways in which philosophy, and especially phenomenology, has tried to develop conceptual tools suitable for describing an area whose unavoidably emotional component seems to escape any conceptualization. Keywords: Dual, Mundane, Relational, Emotionality, Intimacy